(untitled) (Comprehensive Journal of Science, 2025)
This research aims to study the development of marriage, education, and the labor force in Libya during the period from 1973 to 2020, analyze the relationships among them, and identify the challenges facing the country in these areas. The study employed the descriptive–analytical method and relied on secondary sources and statistical data. The results showed an increase in marriage rates, education levels, and labor force participation. However, numerous challenges remain, including unemployment, poverty, and domestic violence. The study recommends strengthening family and marriage support programs, improving the quality of education, enhancing participation in the labor force, combating unemployment and poverty, and promoting the role of women in society. It also suggests developing family and marriage support programs and empowering youth in the community.